The Role of the Amil Zakat Institution to Help Communities Affected by Covid-19 - Fauzul Hanif Noor Athief; Darlin Rizki; Nihayatul Masthuroh; Khaira Gina Yuda Jakti (The Postgraduate of Institut Agama Islam Negeri Metro Lampung, 2023)
The emergence of the Covid-19 pandemic has an impact on the community's economy. The purpose of this research is to find out and explain the active role of amil zakat institutions in collecting and distributing funds. This research was conducted at the Mizan Amanah Solo and Solopeduli institutions. This researcher is a type of qualitative descriptive research. Data collection was carried out by interviewing institutional administrators and communities affected by the pandemic, documentation from journals, books, reports, magazines and so on which were deemed informative. Furthermore, the data obtained was analyzed descriptively to answer the research objectives. The results of this study indicate that the amil zakat institutions Mizan amanah and Solopeduli play an active role in various programs to help communities affected by the pandemic in Surakarta. During the pandemic, the collection of zakat funds at the Mizan Amanah and Solopeduli institutions was carried out online because the average solo community uses social media. The amil zakat institution sells various programs to donors to help and empower communities affected by Covid-19. Mizan Amanah and Solopeduli channeled funds by going directly to the community, with the priority of the community that Mizan Amanah prioritized, namely orphans and the poor, while Solopeduli used the Had Kifayah guidelines. It is important to note that the impact of channeling zakat funds during a pandemic may vary depending on the local context, the scale of disbursement, and the effectiveness of the programs being implemented.